وَصْفُ القُصورِ في عَصْرِ الطَّوائف (القيمة الوثائقيّة) - فارس, عيسى; صَيرَفي, ياسر (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
تتناول هذه الدراسة قصور ملوك الطوائف التي تعرّضَتْ للوصف من قِبَل الشعراء المُوالين للملوك المُجاورين لقصورِهم، وقد تضمّنَتْ وصفاً للقصور من الخارج ومن ثمَّ وَصْفِ موجوداتِها الدّاخلية التي تنمّ عن الرّفعةِ والبهاء لصاحب القصر، ثمّ تمَّ بيان القيمة الوثائقيّة لظاهرة وصف القصور. This study addresses the Tawaif's courts which have been described by poets loyal to kings who are neighboring of their courts, which included a description of the courts from the outside and then describe their assets interior which reflect the greatness and magnificence to the owner of the court, then the value documentary of the courts description phenomenon had represented.